Transcription factor EHF interacting with coactivator AJUBA aggravates malignancy and acts as a therapeutic target for gastroesophageal adenocarcinoma - Li Peng; Yanyi Jiang; Hengxing Chen; Yongqiang Wang; Qiusheng Lan; Shuiqin Chen; Zhanwang Huang; Jingyuan Zhang; Duanqing Tian; Yuntan Qiu; Diankui Cai; Jiangyun Peng; et al. (Elsevier, 2024)
Transcriptional dysregulation of genes is a hallmark of tumors and can serve as targets for cancer drug development. However, it is extremely challenging to develop small-molecule inhibitors to target abnormally expressed transcription factors (TFs) except for the nuclear receptor family of TFs. Little is known about the interaction between TFs and transcription cofactors in gastroesophageal adenocarcinoma (GEA) or the therapeutic effects of targeting TF and transcription cofactor complexes. In this study, we found that ETS homologous factor (EHF) expression is promoted by a core transcriptional regulatory circuitry (CRC), specifically ELF3-KLF5-GATA6, and interference with its expression suppressed the malignant biological behavior of GEA cells. Importantly, we identified Ajuba LIM protein (AJUBA) as a new coactivator of EHF that cooperatively orchestrates transcriptional network activity in GEA. Furthermore, we identified KRAS signaling as a common pathway downstream of EHF and AJUBA. Applicably, dual targeting of EHF and AJUBA by lipid nanoparticles cooperatively attenuated the malignant biological behaviors of GEA in vitro and in vivo. In conclusion, EHF is upregulated by the CRC and promotes GEA malignancy by interacting with AJUBA through the KRAS pathway. Targeting of both EHF and its coactivator AJUBA through lipid nanoparticles is a novel potential therapeutic strategy.